2022
DOI: 10.1002/ajim.23405
|View full text |Cite
|
Sign up to set email alerts
|

On the road again: A cross‐sectional survey examining work schedules, commuting time, and driving‐related outcomes among U.S. oil and gas extraction workers

Abstract: Background Oil and gas extraction (OGE) workers in the United States experience high fatality rates, with motor vehicle crashes the leading cause of death. Land‐based OGE workers drive frequently to remote and temporary worksites. Limited information is available on factors that may influence crash risk for this workforce. Methods A cross‐sectional survey of 500 land‐based OGE workers examined work schedules and hours, commuting, sleep, employer policies, and their relationship to potentially harmful events wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…In the survey mentioned previously, 6 97% of the surveyed OGE workers acknowledged having a safety program or policies, and 25% reported a “lone worker program” through their employer. Lone worker programs may include various approaches to reduce risks of working alone.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In the survey mentioned previously, 6 97% of the surveyed OGE workers acknowledged having a safety program or policies, and 25% reported a “lone worker program” through their employer. Lone worker programs may include various approaches to reduce risks of working alone.…”
Section: Discussionmentioning
confidence: 86%
“…A recent study reported that oil and gas extraction (OGE) workers were more likely than nonmanual workers to drink alcohol excessively, smoke or use smokeless tobacco, and have obesity 4,5 . In a separate survey administered between 2017 and 2019, among 498 OGE workers, 6 the mean age was 36.9 years with nearly half of the respondents (48.4%) older than 34 years, the oldest reported was 70 years. The vast majority were men and more than one third (35.5%) used tobacco daily.…”
mentioning
confidence: 99%
“…The nature and organization of work in the OGE industry predispose workers to an increased state of fatigue. 15,29 Stimulants are known to be commonly used in an effort to extend wakefulness, increase alertness, and counter fatigue. 26,30,31 Cannabis was identified in the positive toxicology screen of four of the decedents.…”
Section: Discussionmentioning
confidence: 99%
“…Decedent case example #2 illustrates these two points by outlining a case where a worker died of stimulant intoxication on the first day on the job and whose symptoms were mistaken for those of heat stress-related illness. The nature and organization of work in the OGE industry predispose workers to an increased state of fatigue 15,29 . Stimulants are known to be commonly used in an effort to extend wakefulness, increase alertness, and counter fatigue 26,30,31 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the well drilling (NAICS code 213111), and service (NAICS code 213112) subsector workers are paid as contractors ¶ who operate, construct, drill, pump, and transport oil and gas ( 2 ). OGE contract workers are often exposed to more hazardous work conditions ( 2 ) and longer shifts ( 3 ), and they experience more work-related fatalities ( 1 , 4 ). Temporary or nonstandard work arrangements have been linked to adverse health and safety outcomes, because in contrast to permanent workers, contract workers often have less information about their work environment, less job-specific training, less access to safety equipment, and no union representation ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%